Surgical Management of Epilepsy in Adolescent Patients - Albert, Gregory W.; Serletis, Demitre (Journal of Pediatric Epilepsy, 2015)
Surgery for the treatment of medically refractory epilepsy remains one of the most effective yet underutilized therapies in all of medicine. The pediatric and adolescent patient population, in particular, stands to benefit from early intervention to achieve the goal of seizure freedom. As per emerging guidelines from the International League Against Epilepsy, patients who now fail as few as two anti-epileptic medication trials should be referred to a surgical epilepsy center for evaluation. For these individuals, surgical intervention has been shown to offer a substantially higher rate of seizure-freedom and improved quality of life, as compared with ongoing medical therapy alone. In this context, we review here the clinical approach to medically intractable epilepsy, including the pre-operative evaluation and surgical options. Our report summarizes several resective surgical strategies including lesionectomy, temporal lobectomy and extra-temporal lobectomy, in addition to hemispherectomy techniques. We also provide an overview of several palliative surgical options, including corpus callosotomy, vagus nerve stimulation and responsive neurostimulation. We then close with a brief discussion of emerging techniques for the minimally invasive surgical epilepsy management. Overall, we advocate for early referral in the pediatric and adolescent population to a comprehensive epilepsy program to establish candidacy for surgical intervention, and we conclude that surgery is safe and effective for the management of epilepsy patients afflicted with medically refractory seizures.
Keywords: intractable epilepsy; invasive electroencephalography monitoring; epilepsy surgery; adolescents